Effect of Renewable Energy and Traditional Energy Production on Economic Growth: The Case of Turkey and Azerbaijan - Huseynli, Nigar (International Journal of Energy Economics and Policy, 2022)
The aim of this study is to determine the relationship between traditional energy and renewable energy in the economic growth of Turkey and Azerbaijan. Multiple Linear Regression Model was used to measure whether there is a significant or insignificant relationship between dependent and independent variables and how these variables affect economic growth. Data for the years 2005-2015 were used in the study. In order to reveal the importance of the model in the analysis process, a series of assumption tests were conducted. The VIF test was used to measure whether the independent variables were related to each other, the Breusch-Godfrey LM test to examine whether there was autocorrelation between the error terms, and the Shapiro-Wilk W test, which is another assumption, was used to measure the normal distribution of the error terms. As a result of the multiple linear regression analysis performed at the end, no relationship was found between renewable energy and economic growth for Azerbaijan, but a significant result was obtained between traditional energy production and economic growth. When we examine the analysis in terms of Turkey, there is no relationship between renewable energy or traditional energy production and economic growth in this country.